Acute and long-term effects of water pipe smoking on the respiratory system: A narrative review - Mogassabi, Waqar; Hassen, Sara; Mahadik, Sahar; Mubarak, Reem; Ibrahim, Wanis (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Tobacco use has become a global major health problem and a leading global cause of preventable death. Water pipe smoking epidemic is on the rise and is replacing cigarettes as the most popular method of tobacco use in many countries. In this narrative review, we aimed to summarize the acute and long-term effects of water pipe smoking on the respiratory system. A comprehensive literature search addressing these effects was conducted without date restrictions. Among the serious acute respiratory effects of water pipe smoking on the respiratory system that have been reported in in literature are acute eosinophilic pneumonia, acute carbon monoxide poisoning, increase in respiratory rate, transmission of infection, and acute deterioration in lung function. Among the long-term effects are the increased risk of lung cancer, chronic obstructive lung disease, asthma and asthma exacerbations, and long-term effects on lung function. The impact of water pipe smoking on the respiratory system and on human health in general deserves more attention from researchers and health policy makers.
Keywords: Lungs; respiratory system; smoking; water pipe